(3eSGFd hCLhHI ef Ydhe eJYOOIs - (3YR GdOjf CHh eMeO YHO GdYRjR Hf YHO GdSdGes
(3ChdgG (B:s
(3eSFdI GdPi hbY ai GdcJGH GdYRjR EMLGLkG ddcaGQ hEKHGJkG dfHhI GdfHi Udi Gddg Ydjg hSde jTcd dCfge jfcQhfg s
(3BNQgG (B:s
(3GdeLGR GdeYbO GdPi jaJbQ ai JUMjMg Edi CehQ cKjQI fMh bhdg YR hLd dG jMH Gddg GdLgQ HGdShA s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeYGQa GdYGeIs